Edukasi Anti Kekerasan sebagai Upaya Mewujudkan Sekolah yang Aman dan Nyaman - Yusup, Wirastiani Binti; Haloho, Oktani; Sihombing, Octa Maria; Muljono, Agus Sutrisno; Marneci, Yuherlita; Anggraini, Riri; Aprinata, Azarya; Mamarimbing, Natanael Yehezkiel (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
School violence is one of the crucial issues that needs serious attention, especially at Purnama High School, Palangka Raya. The increase in cases of violence, both physical and verbal, in the school environment is an urgent problem that needs to be resolved in order to create a safe and conducive learning environment. The purpose of this study is to create a comfortable and safe school through anti-violence education. The method used is Participatory Action Research (PAR) which is carried out based on the stages of to know, to understand, to plan, and to act and reflect. Based on these stages, the results obtained are the conditions faced by Purnama High School are increasing acts of violence in schools, both in verbal and physical forms; efforts made by the school are to provide anti-violence education for students because one of the causal factors is the lack of student knowledge regarding school violence; the results of changes after being given education are that students are active in campaigning through.